A configurable detection chip with ±0.6% Inaccuracy for liquid conductivity using dual-frequency sinusoidal signal technique in 65 nm CMOS. (June 2022) - Lin, Ye; Zhang, Yuejun; Fu, Shengjie; Zhang, Huihong; Wang, Pengjun
Abstract: This paper presents a configurable detection chip for liquid conductivity using a dual-frequency sinusoidal signal technique. The proposed method improves the detection accuracy by effectively avoiding the measurement error caused by polarization effect and capacitance effect. The detection chip mainly includes a small signal amplifier circuit and a data acquisition and processing circuit. First, the small signal amplifier circuit mainly consists of an operational amplifier circuit and a four-choice data selection circuit, which is regulated to implement a configurable function. Through the negative feedback principle, the signal amplification can reach 84.1 dB. Secondly, the data acquisition and processing circuit comprises a SAR ADC and a digital processing unit, with the former being used for signal acquisition and the latter for signal processing. Finally, the detection chip is implemented using TSMC 65 nm CMOS technology. The signal scaling and processing operates at a low area cost of 0.02 μm 2 . The worst-case error for conductivity measurements is ±1.1%, and the worst-case error for the chip configuration is less than 0.6%. The results show that the dual-frequency sinusoidal signal technique and chip configuration can greatly reduce the measurement error.